2005
DOI: 10.1385/ir:31:3:267
|View full text |Cite
|
Sign up to set email alerts
|

Focal Adhesion Kinase–Related Protein Tyrosine Kinase Pyk2 in T-Cell Activation and Function

Abstract: Pyk2 is a protein tyrosine kinase expressed primarily in brain and hematopoietic cells. It becomes activated in response to stimulation through numerous receptors, including integrins, chemokine receptors, and antigen receptors, and is found in association with src-family kinases. Although this enzyme associates with many proteins known to be important for activation and has many characteristics of a scaffolding protein, its function remains elusive. A number of studies in non-T-cells suggest that Pyk2 is impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
87
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(87 citation statements)
references
References 71 publications
0
87
0
Order By: Relevance
“…Thus, different activation patterns of Pyk2, calcium dependent (25) and independent (as concluded from our experiments) are possible. Pyk2 plays an important role in cell morphology, motility, and adhesion in a variety of cells including macrophages (24,42). Its role in inflammation is only beginning to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, different activation patterns of Pyk2, calcium dependent (25) and independent (as concluded from our experiments) are possible. Pyk2 plays an important role in cell morphology, motility, and adhesion in a variety of cells including macrophages (24,42). Its role in inflammation is only beginning to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Proline-rich kinase-2 (Pyk2) 6 and focal adhesion kinase (FAK) 6 are related cytoplasmic protein-tyrosine kinases that contain N-terminal 4.1, ezrin, radixin, moesin (FERM), central kinase, proline-rich, and C-terminal focal adhesion targeting domains (1,2). FAK is abundant and ubiquitously expressed, whereas high level Pyk2 expression is selective and cell typespecific (3).…”
mentioning
confidence: 99%
“…In fibroblasts this difference is due to FAK recruitment and activation at integrin-enriched focal adhesion sites, whereas Pyk2 remains primarily perinuclear-distributed (5). Determining the similarities and differences of FAK-Pyk2 action is an area that remains under investigation (6,7).…”
mentioning
confidence: 99%
“…Recent studies have suggested that non-receptor protein tyrosine kinases play an important role in transducing mechanical stimuli to biochemical pathways by coupling with integrin (Burridge et al 1992;Fukumoto et al 1996;Sieg et al 1998;Schlaepfer et al 1999;Ostergaard and Lysechko 2005;Ramjaun and Hodivala-Dilke 2009). Among them, focal adhesion kinase (FAK) is a non-receptor protein tyrosine kinase that localizes to the point of cell contact with extracellular matrix and has been demonstrated to activate mitogen-activated protein kinases (MAPK) in response to integrin clustering in various types of cells (Burridge et al 1992;Sieg et al 1998;Schlaepfer et al 1999;Ostergaard and Lysechko 2005;Vadali et al 2007;Cai et al 2008).…”
mentioning
confidence: 99%
“…Among them, focal adhesion kinase (FAK) is a non-receptor protein tyrosine kinase that localizes to the point of cell contact with extracellular matrix and has been demonstrated to activate mitogen-activated protein kinases (MAPK) in response to integrin clustering in various types of cells (Burridge et al 1992;Sieg et al 1998;Schlaepfer et al 1999;Ostergaard and Lysechko 2005;Vadali et al 2007;Cai et al 2008). Proline-rich tyrosine kinase 2 (PYK2) is another non-receptor protein tyrosine kinase that has a high sequence homology to FAK, sharing 45% amino-acid sequence identity (Sieg et al 1998;Avraham et al 2000;Rocic et al 2002).…”
mentioning
confidence: 99%